Buried Arc Application in Hybrid Laser-Arc Welding of Thermo-Mechanical Control Process Steels - Wendt Dreveck N. (2024)
© The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature 2023.Hybrid laser arc welding (HLAW) has gained significant attention in recent years due to its ability to provide high-quality welds with improved productivity. One of the key challenges in HLAW is the efficient utilization of the welding arc energy. This work aims to analyze the HLAW process with gas metal buried arc welding (GMBAW), and compare the results obtained with typical results of laser welding and HLAW with non buried arc. Tests were conducted at two welding speeds, 1.0 m/min and 1.5 m/min, and the results were compared with autogenous laser bean welding (LBW) and HLAW without a buried arc, on ASTM A709 steel that was manufactured by Thermo-Mechanical Control Process (TMCP). The buried arc HLAW resulted in a more uniform weld bead, with a reduced heat-affected zone. Moreover, the laser power required to achieve full penetration of the weld joint was smaller for the buried arc HLAW variation.